Flash Flood Climatology in the Lower Region of Southern Sindh - Mahessar, A. A.; Qureshi, A. L.; Siming, I. A.; Kori, S. M.; Dars, G. H.; Channa, M.; Laghari, A. N. (Engineering, Technology & Applied Science Research, 2019)
Climate change impact is felt at a global scale. One of its results is the abnormal rain occurrence during monsoon season. In recent years, visible changes due to unusual weather events in Pakistan’s hydrological cycle were observed in the form of intensification of the hydrological cycle with changing of precipitation events such as floods and prolonged droughts. Hence, abnormal rainfall occurred in regions of southern and northern parts of Sindh, like torrential river floods (2010), flash floods (2011-2012), unpredictable rainstorms, etc. causing loss of lives, damaging infrastructures and crops, structures, and inhabitant displacement. In 2011, heavy cumulative precipitation has been recorded in the southern Sindh districts and the coastal belt of Badin and the LBOD and Kotri surface drainage system achieved their extreme heights. Another example of erratic rain occurred from September 8 to September 13, 2011 and produced an extraordinary discharge of about 14000 cusecs against the designed discharge of 4600 cusecs in the LBOD and Kotri surface drainage systems overtopping drains from several locations and wreaking havoc in the whole area of the southern part of Sindh.